Adverse Drug Events Detected by Clinical Pharmacists in an Emergency Department: A Prospective Monocentric Observational Study. Issue 8 (December 2021) - Laureau, Marion; Vuillot, Olivier; Gourhant, Vincent; Perier, Damien; Pinzani, Véronique; Lohan, Laura; Faucanie, Marie; Macioce, Valérie; Marin, Grégory; Giraud, Isabelle; Jalabert, Anne; Villiet, Maxime; et al.
Abstract : Objectives: Adverse drug events (ADEs) are a major public health issue in hospitals. They are difficult to detect because of incomplete or unavailable medication history. In this study, we aimed to assess the rate and characteristics of ADEs identified by pharmacists in an emergency department (ED) to identify factors associated with ADEs. Methods: In this prospective observational study, we included consecutive adult patients presenting to the ED of a French 2600-bed tertiary care university hospital from November 2011 to April 2015. Clinical pharmacists conducted structured interviews and collected the medication history to detect ADEs (i.e., injuries resulting directly or indirectly from adverse drug reactions and noncompliance to medication prescriptions). Unsure ADE cases were reviewed by an expert committee. Relations between patient characteristics, type of ED visit, and ADE risk were analyzed using logistic regression. Results: Among the 8275 included patients, 1299 (15.7%) presented to the ED with an ADE. The major ADE symptoms were bleeding, endocrine problems, and neurologic disorders. Moreover, ADEs led to the ED visit, hospitalization, and death in 87%, 49.3%, and 2.2% of cases, respectively. Adverse drug event risk was independently associated with male sex, ED visit for neurological symptoms, visit to the ED critical care unit, or ED short stay hospitalization unit, use of blood, anti-infective, antineoplastic, and immunomodulating drugs. Conclusions: This study improves the knowledge about ADE characteristics and on the patients at risk of ADE. This could help ED teams to better identify and manage ADEs and to improve treatment quality and safety.